Capital Commodification in the Field of Tarling Music Digitalization - Imawan, Khaerudin; Shri Ahimsa-Putra, Heddy; Lastoro Simatupang, G.R. Lono (KnE Social Sciences, 2023)
Tarling’s method for creating Tarling music is evolving over time. The digitalization field observes the agents’ ways in production, distribution, and consumption of digital music files. Agents build their own habitus in employing their numerous capitals in the digitalization space. By combining the correlation of habitus and field theories of Bourdieu and Mosco’s perspective on commodification, this research is presented in a qualitative descriptive way with the research locus in the Cirebon region, West Java. The purpose of this research is to find out the commodification practice of Tarling’s music in the digitalization field, including the production, distribution and consumption sub-fields. As a result, commodification is carried out by producer agents, managers, and singers, who tend to be submissive and adaptive to the production structure built through the role of agents in their respective habitus. The production, distribution, and consumption of Tarling music tends to ignore the value of authenticity that the practice of commodification in the digitalization fields produces a pseudo-culture due to standardization and uniformity of form, in which Tarling music becomes a profit commodity. Keywords: commodification, Tarling music, digitalization, Mosco, Bourdieu